Pharmacokinetics of dl-praeruptorin A after single-dose intravenous administration to rats with liver cirrhosis - Zhang, Z (Tehran University of Medical Sciences, 2011)
BACKGROUND AND THE PURPOSE OF THE STUDY: As a novel drug in the treatment of cardiac diseases, dl-praeruptorin A (Pd-Ia) is the major active component of traditional herbal medicine Peucedanum praeruptorum Dunn and is metabolized primarily via cytochrome P450 isozymes (CYP) 3A1 and 3A2 in rats. In the present study, the influence of liver cirrhosis on pharmacokinetics of Pd-Ia and hepatic mRNA expression of CYP3A1 and 3A2 in rats with experimental liver cirrhosis (LC rats) were evaluated. METHODS: Pd-Ia was given intravenously (5 mg kg(−1)) to LC rats induced by dimethylnitrosamine and pharmacokinetic variables were measured. Enzyme kinetic metabolism of Pd-Ia in rat hepatic microsomes was also investigated and hepatic mRNA expression of CYP3A1 and 3A2 were measured by real-time PCR. RESULTS AND MAJOR CONCLUSION: After intravenous administration in LC rats, the area under the plasma concentration-time curve from time zero to infinity (AUC0-8) was significantly greater than that in control rats, which might be due to slower rate of the hepatic blood flow and significant slower hepatic intrinsic clearance (CL(int)) in rats. The decreased metabolic clearance of Pd-Ia in LC rats might be at least partly caused by the decreased levels of CYP3A1 and 3A2 responsible for Pd-Ia metabolism. These findings may provide new insights into the inter- and intra-individual pharmacokinetic variability of Pd-Ia.